IMPLIKASI FUNGSI-FUNGSI MANAJEMEN DALAM SPMI-PT - Reresi, Marsianus (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2012)
This article intends to analyze the implication of management functions in the System of Internal Assurance Quality of High Education. This article deals with the central issue: “What is the implication of various functions of management in the System of Internal Assurance Quality of High Education?” This article argues that the System of Internal Assurance Quality of High Education is guaranteed to work effectively and efficiently as long as it is enhanced by management activity, i.e. by the functions of appropriate planning, organizing, actuating, and controling